2015
DOI: 10.1016/j.bbrc.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and interleukin 1β-induced apoptosis in human umbilical vein endothelial cells involves in down-regulation of monocarboxylate transporter 4

Abstract: Hyperglycaemia and inflammatory can induce apoptosis in vascular endothelial cells, which contributes to the development of vascular complications in diabetes. Endothelial cells depend on glycolysis for their energy metabolism, and monocarboxylate transporters (MCTs) regulate intracellular pH by mediating the influx and efflux of lactate. Here, we evaluate the role of MCT4 in high glucose (HG) and interleukin 1β (IL-1β)-induced apoptosis in human umbilical vein endothelial cells (HUVECs). We demonstrate that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…In addition, based on the degree of mucosal inflammation, we found that forty-three of 54 patients (79.6%) with lactate increased, but no difference among IBD grades ( Figure 1(b) ), which is attributed to various cells, including inflammatory cell, could produce lactate. In line with a study reported by Wang et al, HG and IL-1b decrease MCT4 and its location on plasma membrane as well as increase lactic acid accumulation and apoptosis in HUVECs [ 22 ], suggesting the critical role of inflammation in regulation of MCT4 expression. However, the expression of MCT4 in inflammatory bowel disease remains poorly understood.…”
Section: Resultssupporting
confidence: 90%
“…In addition, based on the degree of mucosal inflammation, we found that forty-three of 54 patients (79.6%) with lactate increased, but no difference among IBD grades ( Figure 1(b) ), which is attributed to various cells, including inflammatory cell, could produce lactate. In line with a study reported by Wang et al, HG and IL-1b decrease MCT4 and its location on plasma membrane as well as increase lactic acid accumulation and apoptosis in HUVECs [ 22 ], suggesting the critical role of inflammation in regulation of MCT4 expression. However, the expression of MCT4 in inflammatory bowel disease remains poorly understood.…”
Section: Resultssupporting
confidence: 90%
“…Aldose reductase inhibitors slightly suppressed Slc16a4 mRNA levels in the absence of TNF-α, and TNF-α stimulation resulted in an additional suppression, which was not affected by aldose reductase inhibitors ( Figure 7H). Consistently, MCT4 levels have been shown to be reduced by IL-1β in endothelial cells (39). TNF-α-induced GLUT1 also was not altered by aldose reductase inhibitors ( Figure 7I).…”
Section: Resultssupporting
confidence: 72%
“…Hyperglycemia plays a central role in the pathogenesis of diabetic vascular complications [2,3], which are the leading cause of morbidity and mortality in patients with diabetes. At cellular level, high glucose can induce apoptotic response in endothelial cells and lead to endothelial damage [4]. Compelling evidence indicates a link between high glucose-induced apoptosis of endothelial cells and reactive oxygen species (ROS) production [5].…”
Section: Introductionmentioning
confidence: 99%